Spatial concentration of Indian service industries in rural and urban areas: A micro-unit-level analysis - Sugam Agarwal; Smruti Ranjan Behera (Cogent Economics & Finance, 2023)
This paper explores the spatial concentration of 120 service industries in India's rural and urban areas, covering 33.60 million establishments using Economic census (2013) data at the district level. Besides, this study uses a cartogram map to examine knowledge-intensive business services (KIBS) industries' spatial concentration patterns and geographical concentration of employment of workers in rural and urban areas in India. Empirical results show that the magnitude of the spatial concentration effect varies in rural and urban areas. Further, empirical results reveal that KIBS industries are localized in rural and urban areas but have a skewed distribution toward urban areas. Moreover, results show that hotspots in rural areas seem higher than urban hotspots, although rural hotspots employ fewer employees than urban hotspots. The empirical results suggest that urban planners and district municipal authorities can give more emphasis and implement suitable KIBS industry-specific policies to boost regional economic growth and employment in rural and urban India.
Keywords: L80; O30; R12; 330; knowledge-based; service industries; spatial concentration; Urban-rural